Cross-sectional prospective feasibility study of newborn screening for sickle cell anaemia and congenital hypothyroidism in Guyana. Issue 2 (22nd February 2022) - Alladin, Bibi Areefa; Mohamed-Rambaran, Pheona; Grey, Vijay; Hunter, Andrea; Chakraborty, Pranesh; Henderson, Matthew; Milburn, Jennifer; Tessier, Laurie
Abstract : Introduction: Newborn screening (NBS) is a test done shortly after birth to detect conditions that cause severe health problems if not treated early. An estimated 71% of babies worldwide are born in jurisdictions that do not have an established NBS programme. Guyana currently has no NBS programme and has established a partnership with Newborn Screening Ontario (NSO) to initiate screening. Objectives: To assess the feasibility of implementing a NBS programme in Guyana for congenital hypothyroidism (CH) and haemoglobinopathies (HBG) and to report on screen positive rates and prevalence (Hardy-Weinberg equilibrium (HWE)) for CH and HBG. Methods: Term, healthy Guyanese infants were evaluated (with consent) using heel prick dried blood spots (DBS) shortly after birth (closer to 24 hours of life). DBS samples were analysed at NSO. Screening test for CH was done using a human thyroid-stimulating hormone (hTSH) assay. Mean hTSH levels between the Guyanese sample and the Ontarian population were compared using Student's t-test with an alpha of 0.05. Screening test for HBG was performed with a cation-exchange high-performance liquid chromatography. Results: The pilot was conducted from 6 June 2016 to 22 September 2017. Georgetown Public Hospital Corporation recruited 2294 mothers/infants. Screen positive rate for CH in our sample was 0.0% (0/2038 infants). Mean TSH levels in Guyanese samples (1.7 µU/mL blood) was noticed to be significantly different than in the Ontarian population (4.3 µU/mL blood) (p<0.05). Screen positive rate for sickle cell anaemia (SCA) in our sample was 0.3% (7/2039 patients), and the carrier rate was 8.4% (172/2039 patients). Using the HWE, the SCA frequency (S allele frequency) 2 is 0.049 2 =0.002 Conclusion: NBS for CH and SCA in Guyana could be beneficial. Future work should focus on conducting larger pilots which could be used to inform diagnosis and treatment guidelines for Guyanese people.